From the modern to the postmodern: gender in Cuban cinema, 1974-1990 - Baron, Guy (2009)
The Instituto Cubano del Arte e Industria Cinematogräficos (ICAIC) was the first cultural institution to be created by the new Cuban revolutionary government in 1959. One of its aims was to create a revolutionary cinema to suit the needs of the Revolution in a climate of transformation and renewal. At the same time, issues of gender equality and gender relations became extremely important in a revolution attempting to eradicate some of the negative social tendencies of the past.